Quality of support in perioperative management and care for Palestinians with autism - Nouran Yahya; Firdaous Jawadeh; Shahd Rawajbeh (My University, 2021)
Background: Medical students are the future workforce of physicians in primary, secondary, tertiary, and highly specialized care centers. The present study was undertaken to assess familiarity, knowledge, confidence, of medical students with regard to autism spectrum disorders (ASDs). Methods: This multicenter study was conducted in a cross-sectional design among medical students in the 3 main universities in Palestine. In addition to the sociodemographic and academic details, the questionnaire measured familiarity (8-items), knowledge (12-items), confidence and willingness to learn (5-items) with regard to ASDs. Results: The questionnaire was completed by 309 medical students (response rate = 77.3%). The median familiarity, knowledge, and confidence scores were 50% (42.5%, 57.5%), 50% (41.7%, 66.7%), and 60.0% (54.0%, 68.0%), respectively. There was a positive moderate correlation between familiarity and knowledge scores (Spearman’s rho = 0.29, p-value < 0.001) and familiarity and confidence scores (Spearman’s rho = 0.34, p-value < 0.001). Medical students who have received a course on autism were 3.08-fold (95% C.I. of 1.78-5.31) more likely to score ≥ 50% on the familiarity items compared to those who did not receive a course. The medical students who were in their clinical academic stage, who received a course on ASDs, and those who interacted with individuals with ASDs were 2.36-fold (95% C.I. of 1.34-4.18), 2.66-fold (95% C.I. of 1.52-4.65), and 2.59-fold (95% C.I. of 1.44-4.63) more likely to score ≥ 50% on the knowledge items. Medical students who reported high satisfaction with their social life were 2.84-fold (95% C.I. of 1.15-7.00) more likely to score ≥ 50% on the confidence items. Conclusion: The present study identified considerable awareness and knowledge gaps among medical students with regard to ASDs. Medical students in this study reported low confidence in their ability to provide healthcare services to individuals with ASDs. Appropriately designed educational interventions might improve familiarity, knowledge, and confidence of medical students. More studies are still needed to investigate if such interventions can improve healthcare services for individuals with ASDs.
Keywords: Autism spectrum disorders, Awareness, Knowledge, Education, Medical students